2022
DOI: 10.1039/d2nr04272j
|View full text |Cite
|
Sign up to set email alerts
|

Facile and scalable fabrication of exosome-mimicking nanovesicles through PEGylated lipid detergent-aided cell extrusion

Abstract: We report a scalable fabrication method to generate exosome-mimicking nanovesicles (ENVs) using a biocompatible, cell-binding lipid detergent during cell extrusion. A PEGylated mannosylerythritol lipid (MELPEG) detergent was rationally engineered to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Through these modifications, we demonstrated an improved production of AEV P‑MEL , increasing particle production approximately 2.7 times while maintaining its vesicular morphology at the nanometer scale (Figures c,d and S4a–c). A previous study confirmed through quartz crystal microbalance with dissipation (QCM-D) analysis that the P-MEL strongly associated with phospholipid membranes, resulting in increased cell membrane deformability and the AEV production yield . The biocompatibility investigation of MEL, P-MEL, and AEV P‑MEL at various molar concentrations revealed that both P-MEL obtained by the PEGylation of MEL and AEV P‑MEL obtained using P-MEL exhibited improved cell viability (Figure e).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Through these modifications, we demonstrated an improved production of AEV P‑MEL , increasing particle production approximately 2.7 times while maintaining its vesicular morphology at the nanometer scale (Figures c,d and S4a–c). A previous study confirmed through quartz crystal microbalance with dissipation (QCM-D) analysis that the P-MEL strongly associated with phospholipid membranes, resulting in increased cell membrane deformability and the AEV production yield . The biocompatibility investigation of MEL, P-MEL, and AEV P‑MEL at various molar concentrations revealed that both P-MEL obtained by the PEGylation of MEL and AEV P‑MEL obtained using P-MEL exhibited improved cell viability (Figure e).…”
Section: Resultsmentioning
confidence: 99%
“…31,32 Taking advantage of a glycolipid produced by the yeast Pseudozyma 33 as an effective inhibitor for inflammatory molecules, mannosylerythritol lipids (MELs) were conjugated with PEG (P-MEL) via the thiol-maleimide reaction. 34,35 Thereafter, anti-inflammatory artificial extracellular vesicles, referred to as AEV P-MEL , were fabricated using the cell extrusion method, in which the cell membrane is decomposed and self-assembled as primary human keratinocytes pass through sequential membrane filters. 35,36 Through in vitro and in vivo studies, we aimed to prove the therapeutic potential of AEV P-MEL in PM-induced skin inflammation, as illustrated in Figure 1.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations